Regional Symbols of Russian North: on Material of Collocations with Toponymic Component - Y. A. Krivoshchapova (Научный диалог)
Semantic and motivational analysis of collocations with the toponymic component ( Vologda butter , Mezen painting , Kargopol ginger , Shemogsa carving , etc.) is proposed. The author examines such structures as the linguistic component of the regional cultural brand. The paper is focused on the Northern territories of European part of Russia (the Russian North). It is emphasized that not all such names become territorial “logo,” but only those which are frequent, have semantic and metaphoric “sufficiency” and present in the consciousness of a native speaker in the form of “visiting card” of the region. It is noted that the status of such units in the language system has not been fully determined: they are not fixed nor by dialect, nor phraseological dictionaries. The author draws attention to the fact that, being used in collocations, adjectives derived from toponyms can have the function of appraisal characteristics: they lose their geographical reference and are endowed with the generalized-meliorative connotations ( Vologda butter = a high quality butter). It is noted that seme ‘high quality product’ is shown at the level of contextual semantics, when toponymic attributive means the best product of the proposed “on the market.” The author points out that, in addition to evaluative connotations, seme ‘typically Russian, national’ can be also expressed in the contexts.